Nationalism, ethnicity and the state : making and breaking nations - Coakley, John (London : SAGE, 2012)
This textbook offers students a truly comprehensive and engaging account of the vibrant topic of nationalism.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Nationalism